2011
DOI: 10.1038/aja.2011.20
|View full text |Cite
|
Sign up to set email alerts
|

Sperm donation and its application in China: a 7-year multicenter retrospective study

Abstract: Sperm donation in China is different from that in other countries due to cultural, social and political factors. This research presents the current status of sperm donation in Mainland China and highlights some problems. Between January 2003 and December 2009, 19 471 sperm donors were screened totally and 6467 donors (33.2%) were recruited. The primary reasons for non-recruitment were either inadequate semen parameters (55.0%) or positive results for sexually transmitted diseases (7.9%). There were 327 (1.7%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…This is in agreement with the findings of Lui et al who reported that about 69% of their respondents had expected financial reward (8). Ping et al also reported that monetary reward was a motivating factor for semen donors in China (9). Studies in the UK and other countries have clearly indicated that payment for sperm donation is an important consideration, particularly among students, this seem to be the pattern in this study (10).…”
Section: Discussionsupporting
confidence: 57%
“…This is in agreement with the findings of Lui et al who reported that about 69% of their respondents had expected financial reward (8). Ping et al also reported that monetary reward was a motivating factor for semen donors in China (9). Studies in the UK and other countries have clearly indicated that payment for sperm donation is an important consideration, particularly among students, this seem to be the pattern in this study (10).…”
Section: Discussionsupporting
confidence: 57%
“…Based on our statistical study of a large sample size, however, the correlation between the three parameters and the progressive motility recovery rate existed. As these three factors are major parameters in evaluating semen quality during sperm donation (World Health Organization, ; Hu et al ., ; Ping et al ., ), our results indicate that the quality evaluation of semen during donation is an effective process to assure good progressive motility recovery rate in sperm bank processing.…”
Section: Discussionmentioning
confidence: 54%
“…Artificial insemination with donor spermatozoon (AID) is an assisted reproductive technology that introduces donor semen into a female's uterus or cervix for the purpose of achieving a pregnancy through in vivo fertilisation other than sexual intercourse (Qiao, ). As AID technology has been gradually accepted, there is an increasing number of offspring conceived by AID technology, and therefore, more and more attention has been paid to the health status of the offspring (Liang et al ., ; Ping et al ., ). In this study, we retrospectively analysed the offspring conceived by AID technology and the offspring delivered by women who conceived naturally in the same period to provide evidence for safety evaluation of the AID technology.…”
Section: Introductionmentioning
confidence: 97%